Red blood cell to platelet ratio and its trajectory as prognostic factors for patients with gastrointestinal tract perforation and abdominal sepsis - Jie Zhao; Junkun Zhang; Jixiu Fan; Heihei Li; Weidong Wu; Jifang Liang (PLoS ONE, 2025)
Background Sepsis after emergency gastrointestinal perforation surgery increases costs and hospital stay. Early diagnosis and management are vital. This study assesses the prognostic value of the red blood cell to platelet ratio (RPR) in these patients with abdominal sepsis. Method Clinical data from MIMIC-IV and a hospital validation set were retrospectively analyzed. Demographics, comorbidities, and lab indices were extracted; missing values were imputed using random forest. RPR’s dynamic changes and relation to prognosis were analyzed using latent category trajectory modeling. Prognostic factors were screened via Lasso-Cox regression to build column-line graph models. Kaplan-Meier, log-rank tests, and restricted cubic splines analyzed RPR-outcome associations. R 4.2.3 was used; P < 0.05 was significant. Results A total of 243 patients were enrolled in MIMIC-IV and 253 patients were enrolled in the hospital. RPR was a significant prognostic indicator. Elevated RPR correlated with coagulation dysfunction (increased PT/INR, decreased fibrinogen) and higher mortality risk. Trajectory analysis identified two RPR patterns; Class 1 had significantly lower 28-day mortality than Class 2. The hospitalization and ICU prognostic models demonstrated good efficacy. Validation set results supported these findings, indicating dynamic RPR changes effectively assess prognosis. Conclusions The red blood cell to platelet ratio may serve as a novel prognostic biomarker for abdominal septic patients, influencing clotting and kidney function.